Children and media : a global perspective - Lemish, Dafna, 1951- (West Sussex, UK ; Malden, MA : Wiley-Blackwell, 2015)
"Taking a global and interdisciplinary approach, Children and Media explores the role of modern media, including the internet, television, mobile media and video games, in the development of children, adolescents, and childhood. Primer to global issues and core research into children and the media integrating work from around the world Comprehensive integration of work that bridges disciplines, theoretical and research traditions and methods Covers both critical/qualitative and quantitative approaches to the topic "--
"Children and Media is the definitive overview of the intersection of children and media, providing a sweeping picture of the field from the accumulated interdisciplinary and global literature of the past 60 years. The text is a comprehensive integration of different theoretical traditions and research practices, and one of the only books on the market to cover both critical, qualitative, and quantitative approaches to the topic. It brings together developmental psychology, cultural studies, sociology of childhood, and health studies, among others, providing an understanding of the roles media have in the changing nature of childhoods around the world. The author covers the entire scope of media that children are exposed to, including television, internet, video games, and mobile media"--
5. Media and perceptions of self and society -- Media and gender -- Construction of gender roles -- Construction of gender identity -- Gay identities -- The social construction of reality -- Violence and the "mean world" hypothesis -- Materialism -- Perceptions of "us" in comparison to "others" -- Cultural integration of immigrant children -- The construction of political reality -- The construction of conflicts -- Peacebuilding interventions -- Edutainment genres -- Americanization and globalization -- What is "America"? -- 6. Media, sociality and participation -- Social networking -- Comparing offline and online relationships -- Marginalized identities -- Risk and harm -- Cyberbullying -- Organized production and participation -- Civic engagement and activism -- 7. Media literacy education -- The central debates in media literacy education -- Media literacy education around the world -- Practical aspects of media literacy education -- The curriculum -- Teaching -- Assessment -- Evaluating media literacy education -- 8. Policy and advocacy -- Criteria for quality media -- Broadcasting policy for children -- Content-related policy issues -- Violence and sexually explicit content policy -- Television advertising policy -- Convention on television broadcasting for children and youth -- Internet-related policy issues -- Interventions on behalf of children -- Conclusions : growing up with media -- The changing nature of childhood -- Research involvement in debate -- Neither good nor bad.
Includes bibliographical references (pages 243-267) and index.
Keywords: Mass media and children